2005
DOI: 10.1097/01.mcg.0000173930.60115.62
|View full text |Cite
|
Sign up to set email alerts
|

Uses of Photodynamic Therapy in Premalignant and Malignant Lesions of the Gastrointestinal Tract Beyond the Esophagus

Abstract: Much has recently been written regarding the use of photodynamic therapy for the treatment of esophageal carcinoma and dysplastic Barrett's esophagus. This review, however, describes the clinical experience using photodynamic therapy with various photosensitizer agents for the treatment of diseases in other areas of the gut, especially the pancreaticobiliary tract where European studies have established the role of porfimer sodium photodynamic therapy in the management of patients with cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 140 publications
0
7
0
2
Order By: Relevance
“…169 Early clinical studies from Japan of PDT in the stomach suggested great promise 170-171 , but regrettably were not followed by randomized clinical trials so far. PDT for early duodenal and ampullary cancers and advanced adenomas has been also investigated in pilot studies that indicated promising results, but further work is required to optimize the treatment conditions.…”
Section: Clinical Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…169 Early clinical studies from Japan of PDT in the stomach suggested great promise 170-171 , but regrettably were not followed by randomized clinical trials so far. PDT for early duodenal and ampullary cancers and advanced adenomas has been also investigated in pilot studies that indicated promising results, but further work is required to optimize the treatment conditions.…”
Section: Clinical Pdtmentioning
confidence: 99%
“…Consequently, a multicenter clinical trial has been recently initiated to obtain regulatory approval in the USA and Canada. 169 …”
Section: Clinical Pdtmentioning
confidence: 99%
“…The clinical impact of m THPC and other PS in the treatment of gynecological diseases and head & neck cancer has been discussed (301–303). Reviews on skin cancer (basal cell carcinoma [BCC]) (304) as well as gastrointestinal and esophageal (305–308), brain (309), prostate (9,310), pancreas (311), breast (312), urological malignancies in general (313,314) and new treatment options thereof (315) and gynecological (316) malignancies show that these cancers can be treated with a reasonable degree of success with Temoporfin. A review by Konan et al.…”
Section: Clinical Experiencementioning
confidence: 99%
“…Photodynamic therapy (PDT) is an approved treatment for a variety of malignant diseases and has been used in clinical studies including brain, prostate, breast, pancreas, rectum, head and neck cancer, and Barrett's esophagus with dysplasia (1)(2)(3)(4)(5)(6). Preclinical interstitial (IS) PDT studies have also been performed in parallel and include brain tumors (7), vertebral metastases (8), and prostate cancer (9).…”
Section: Introductionmentioning
confidence: 99%